Law enforcement towards the management of the forestry mangrove Province South Sulawesi - Prof Syahruddin Nawi; Hikmawati Mustamin; Ilham Abbas; Sultang Sultang (Indonesia Prime, 2018)
This research aims to find out Nature of law enforcement In Physical Education Mangrove forests in southern Sulawesi. In addition to identifying and analyzing the factors influencing law enforcement efforts in the conservation of mangrove forests in southern Sulawesi and in finding a strategy or enforcement of a new model law while preserving Mangrove forests in southern Sulawesi. The results showed that the first, espionage and legal compliance against a regulatory and forestry legal environment are being perfected together in an attempt to actively enforce the law that is ravaged, preventively and oppressive in efforts to conserve mangrove forests in the South Sulawesi. The level of support and legal compliance against the rule of law is at a high level of four category categories (Low, medium, high and very Tinggi). This indicates that the people of De Sulawesi are obedient and obey related laws against purveying mangrove forests. Secondly, Factors that constrain law enforcement efforts in the communities existance from the negative behavior of law enforcement officials who became disoriented against those who harmed the harm of mangrove plant persons. However Therefore Of Behind it, a supporting factor in an effort to enforce Community law is to recognize the community that supports law enforcement to be a moral commitment